2020
DOI: 10.1001/jamaoto.2020.0001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Residual Disease Following Transcanal Totally Endoscopic vs Postauricular Surgery Among Children With Middle Ear and Attic Cholesteatoma

Abstract: IMPORTANCE Transcanal totally endoscopic ear surgery (TEES) improves tympanic cavity visibility during cholesteatoma resection but does not readily permit 2-handed surgery, which is possible with a postauricular approach and use of an operating microscope. Improved visibility and 2-handed access may reduce rates of incomplete surgical clearance and residual cholesteatoma.OBJECTIVE To compare rates of residual cholesteatoma after TEES vs those after open surgery with a postauricular approach for initial disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
(43 reference statements)
0
22
0
2
Order By: Relevance
“…The duration of surgery was compared in 21 of these studies, 13 of which reported a shorter surgical time in the endoscopic technique. 14,16,[18][19][20][21][22][24][25][26][27][28][29][30][31][33][34][35][36] The postoperative recovery time and level of pain presented by patients were evaluated by nine retrospective studies, seven of which had a 39 Retrospective TEES may be an alternative to a postauricular approach for removal of cholesteatoma limited to the middle ear and/or the attic in children. 18 Retrospective Similar results for ET and MT approach without significant statistical differences.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of surgery was compared in 21 of these studies, 13 of which reported a shorter surgical time in the endoscopic technique. 14,16,[18][19][20][21][22][24][25][26][27][28][29][30][31][33][34][35][36] The postoperative recovery time and level of pain presented by patients were evaluated by nine retrospective studies, seven of which had a 39 Retrospective TEES may be an alternative to a postauricular approach for removal of cholesteatoma limited to the middle ear and/or the attic in children. 18 Retrospective Similar results for ET and MT approach without significant statistical differences.…”
Section: Resultsmentioning
confidence: 99%
“…20,21 However, although the recidivism rate in endoscopy surgery has been shown to be lower, the global rate of residual and recurrent cholesteatoma has not reached 0 per cent. 2224 Another major cause of residual disease is incomplete cleaning of the matrix. Typical examples are cholesteatomas remaining around the ossicles or on bony defects of the middle cranial fossa, labyrinth and fallopian canal.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, transcanal endoscopic ear surgery (TEES) has been popularly applied to different types of middle ear disease. 12 TEES has many advantages, including a wide field of view, higher magnification of delicate anatomical structures, and clear visualization of anatomical areas located in blind spots when viewed through a microscope. 13 , 14 , 15 Consequently, TEES is thought to be less invasive than microscopic ear surgery (MES).…”
Section: Introductionmentioning
confidence: 99%